Distribution of Type 2 Diabetes Mellitus Patients Based on Doshas and Pirakiruti - Kumutharanjan, T.; Ramiah, S.; Arasaratnam, V. (University of Jaffna, 2022)
The human body is made up of dehaparamanu (cell). In each and every cell, three Doshas namely Latham, Pitham and Kapham coexist and function harmoniously. Based on Doshas, the lifespan is divided into three periods in Siddha System. They are Kapha (up to 33 years of age), Pitha (34-<66 years of age) and Vatha (>66-99 years of age) periods. Treatment based on Siddha Philosophy is aimed at keeping Latham, Pitham and Kapham in equilibrium by correcting the imbalance by administering a drug, which is predominately of the opposite nature. As such it is a necessary to assess the Pirakiruti (Psychosomatic condition) of the subjects for effective treatment. In a study conducted recently with 193 type 2 diabetes mellitus patients, the occurrence of diabetes mellitus based on Doshas and Pirakiruti was assessed. Among the diabetic patients 161 and 32 respectively belonged to the Pitha and Vatha periods. None of the patients belonged to the Kapha period. There were more male diabetics (90) than females (71) in the Pithaas well as Vatha (25 males and 7 females) periods. The percentages of the males in Pitha and Vatha periods among the entire patients were 46.63 and 12.95 respectively while among the females were 36.78 and 3.63 respectively. The assessment of Pirakiruti of the subjects depends on the specific features based on Doshas. According to the different combinations of the features there were 68 VathaPirakirutipatients of whom 59% showed VathaDosha features, 23.5% PithaDosha features and 17.5 % of KaphaDosha features. Likewise, among 74 patients with Pitha Pirakiruti64.7% showed features of PithaDhosa, 29.4% VathaDosha features and 5.9% KaphaDosha features. Moreover, among 51 patients with KaphaPirakiruti, 55% showed features of Kapha Dosha, 25% Vatha Dosha features, and 20% of Pitha Dosha features. According to Pirakiruti, Pitha Pirakiruti (52 males and 22 females) subjects were higher than other Pirakiruties with lowest number in KaphaPirakiruti (29 males and 22 females). Among the 68 Vatha Pirakiruti patients there were equal number of males and females. The results of the present study could not be compared as studies of similar nature have not been reported.
Keywords: Type 2 diabetes mellitus; Pirakiruti; Dosha